Transformation of a Microprolactinoma into a Mixed Growth Hormone and Prolactin-Secreting Pituitary Adenoma - DESSIMOZ, CEDRIC; BROWAEYS, PATRICK; MAEDER, PHILIPPE; LHERMITTE, BENOIT; PITTELOUD, NELLY; MOMJIAN, SHAHAN; PRALONG, FRANCOIS P. (Frontiers in Endocrinology, 2012)
Combined prolactin (PRL) and growth hormone (GH) secretion by a single pituitary tumor can occur in approximately 5% of cases. However, in all previously reported patients, combined secretion of both hormones was present at the time of diagnosis. Here we describe a patient initially diagnosed with a pure prolactin-secreting microadenoma, who experienced the progressive apparition of symptomatic autonomous GH secretion while on intermittent long term dopamine agonist therapy. She was operated on, and immunohistochemical analysis of tumour tissue confirmed the diagnosis of pituitary adenoma with uniform co-staining of all cells for both GH and PRL. This patient represents the first documented occurrence of asynchronous development of combined GH and PRL secretion in a pituitary adenoma. Although pathogenic mechanisms implicated remain largely speculative, it emphasizes the need for long term hormonal follow up of patients harboring prolactinomas.